2019
DOI: 10.1103/physrevlett.122.140601
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Fluctuations in Microscopic Machines

Abstract: Nanoscale machines are strongly influenced by thermal fluctuations, contrary to their macroscopic counterparts. As a consequence, even the efficiency of such microscopic machines becomes a fluctuating random variable. Using geometric properties and the fluctuation theorem for the total entropy production, a "universal theory of efficiency fluctuations" at long times, for machines with a finite state space, was developed in [Verley et al., Nat. Commun. 5, 4721 (2014); Phys. Rev. E 90, 052145 (2014)]. We extend … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…The efficiencies of individual trajectories are subject to fluctuations, and can be negative or even exceed one, although these fluctuations (inaccessible in macroscopic systems) are unlikely. 155,156 When the only output is work against an external force f ext , the efficiency is 135,150,157,158…”
Section: Efficiencymentioning
confidence: 99%
“…The efficiencies of individual trajectories are subject to fluctuations, and can be negative or even exceed one, although these fluctuations (inaccessible in macroscopic systems) are unlikely. 155,156 When the only output is work against an external force f ext , the efficiency is 135,150,157,158…”
Section: Efficiencymentioning
confidence: 99%
“…A highly interesting problem is a possible thermodynamic interpretation of the path probability ratio ΔΣ[x] [18], e.g., via exploring its connection to active pressure [14,52], to the different phases observed in active matter [53], or to the arrow of time [54,55] in these systems. Such a thermodynamic interpretation, in particular concerning the role of dissipation, may finally allow to quantify efficiency fluctuations in stochastic heat engines operating between active baths [56], in analogy to passive stochastic heat engines [57][58][59]. Other important questions which can be approached directly by using our general result for the path weight p[x] include the analysis of the response behavior under external perturbations [43] or of violations of the fluctuation-response relation [60,61] due to the inherent nonequilibrium character of active matter, and their potential for probing properties of the active fluctuations [61].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that the stochastic efficiency of Brownian heat engines driven by the non-equilibrium protocol is not bounded and can even exceed Carnot efficiency [51][52][53][54][55][56][57][58]. Here, we study the stochastic efficiency η; À βW=I of the information engine owing to the fluctuations in work and mutual information (Figure 3).…”
Section: Efficiency Fluctuationsmentioning
confidence: 99%